Zakat vs Tax: A Maqasid Sharia Perspective - Pratama, Muhammad Rifky; Mukhlisin, Murniati; Azid, Toseef (Journal of Islamic Economics and Finance Studies, 2024)
This study explores the comparison between zakat and tax within the framework of maqasid sharia perspective.  Specifically, this study compares zakat and tax in terms of how effectively each system fulfills the objectives (maqasid ) of sharia such as hifz al-mal (protection of wealth), islah (rectification), hifz al-nafs (salvation of the soul), and 'adl (social justice). It aims to evaluate the extent of the impact of zakat and tax implementation on wealth distribution, poverty elimination, and the establishment of a just economic structure. Through a comprehensive analytical approach, this study evaluates the contribution of each instrument towards the realization of these objectives. A qualitative approach and a thematic literature review is adopted to explore evidences related to zakat vs tax from a maqasid sharia perspective. The result shows that zakat proves to be an effective tool in supporting equitable wealth distribution and social safety, while taxes provide consistent funding for public services. However, challenges such as compliance, transparency and fairness remain a critical focus. This research provides important insights into how the implementation of zakat and tax can be optimized to achieve the desired balance within the maqasid sharia framework.